Genetic diversity of VIR Raphanus sativus L. collections on aluminum tolerance - A. B. Kurina; I. A. Kosareva; A. M. Artemyeva (Вавиловский журнал генетики и селекции, 2020)
Radish and small radish (Raphanus sativus L.) are popular and widely cultivated root vegetables in the world, which occupy an important place in human nutrition. Edaphic stressors have a significant impact on their productivity and quality. The main factor determining the phytotoxicity of acidic soils is the increased concentration of mobile aluminum ions in the soil solution. The accumulation of aluminum in root tissues disrupts the processes of cell division, initiation and growth of the lateral roots, the supply of plants with minerals and water. The study of intraspecific variation in aluminum resistance of R. sativus is an important stage for the breeding of these crops. The purpose of this work was to study the genetic diversity of R. sativus crops including 109 accessions of small radish and radish of various ecological and geographical origin, belonging to 23 types, 14 varieties of European, Chinese and Japanese subspecies on aluminum tolerance. In the absence of a rapid assessment methodology specialized for the species studied, a method is used to assess the aluminum resistance of cereals using an eriochrome cyanine R dye, which is based on the recovery or absence of restoration of mitotic activity of the seedlings roots subjected to shock exposure to aluminum. The effect of various concentrations on the vital activity of plants was revealed: a 66-mM concentration of AlCl3 · 6Н2О had a weak toxic effect on R. sativus accessions slowing down root growth; 83 mM contributed to a large differentiation of the small radish accessions and to a lesser extent for radish; 99 mM inhibited further root growth in 13.0 % of small radish accessions and in 7.3 % of radish and had a highly damaging effect. AlCl3 · 6Н2О at a concentration of 99 mM allowed us to identify the most tolerant small radish and radish accessions that originate from countries with a wide distribution of acidic soils. In a result, it was possible to determine the intraspecific variability of small radish and radish plants in the early stages of vegetation and to identify genotypes that are contrasting in their resistance to aluminum. We recommend the AlCl3 · 6Н2О concentration of 83 mM for screening the aluminum resistance of small radish and 99 mM for radish. The modified method that we developed is proposed as a rapid diagnosis of aluminum tolerance for the screening of a wide range of R. sativus genotypes and a subsequent study of contrasting forms during a longer cultivation of plants in hydroponic culture (including elemental analysis of roots and shoots, contrasting in resistance of accessions) as well as reactions of plants in soil conditions.